2021
DOI: 10.1136/rmdopen-2020-001450
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and distribution of peripheral musculoskeletal manifestations in spondyloarthritis including psoriatic arthritis: results of the worldwide, cross-sectional ASAS-PerSpA study

Abstract: ObjectivesTo characterise peripheral musculoskeletal involvement in patients with spondyloarthritis (SpA) including psoriatic arthritis (PsA), across the world.MethodsCross-sectional study with 24 participating countries. Patients with a diagnosis of axial SpA (axSpA), peripheral SpA (pSpA) or PsA according to their rheumatologist were included. The investigators were asked which diagnosis out of a list of six (axSpA, PsA, pSpA, inflammatory bowel disease-associated SpA, reactive arthritis or juvenile SpA (Juv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
79
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 29 publications
6
79
1
2
Order By: Relevance
“…A total of 3835 participants from 23 countries were eligible for this analysis (no participants from the UK due to administrative limitations [9]). The mean age was 42 years (SD 12) with 61% males.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 3835 participants from 23 countries were eligible for this analysis (no participants from the UK due to administrative limitations [9]). The mean age was 42 years (SD 12) with 61% males.…”
Section: Resultsmentioning
confidence: 99%
“…The ASAS-perSpA (peripheral involvement in SpA) study design has been described previously [9]. It was an international, cross-sectional study with 24 contributing countries that recruited from 2018-2020.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, peripheral arthritis appeared again in clinical descriptions (48). An international study of 4,465 patients with SpA found that nearly 70% of the participants had at least one episode of peripheral arthritis (48,60). Data splitting yielded 57% with arthritis, enthesitis in 44%, and dactylitis in 15%.…”
Section: The Tarsitis Link With Spamentioning
confidence: 99%
“…A recent worldwide survey reported that hip involvement across the spectrum of SpA varied from 27% in those with psoriatic arthritis up to 53% in juvenile SpA, being more common among Asian patients. [ 7 ] These very recent data suggest that the prevalence of hip involvement at least in SpA may not have changed over time, since previous cohorts have reported a 24% to 36% variation in prevalence of hip involvement in AS. [ 3 ] However, there are no prospectively collected data evaluating severity of hip damage in AS, let alone in the whole SpA spectrum of diseases.…”
mentioning
confidence: 96%
“…[ 1 ] Despite these data, there are no explicit recommendations in the current guidelines to start bDMARDs early in a patient with AS and groin pain. [ 8 , 7 ]…”
mentioning
confidence: 99%